QualiSy characteristics and their interrelationships in Indian rapeseed-mustard (Brassiea sp) varieties* - CHAUHAN, J S; BHADAURIA, V P S; SINGH, MAHARAJ; SINGH, K H; KUMAR, ARVIND (The Indian Journal of Agricultural Sciences, 2011)
Quality characteristics of 96 Indian rapeseed-varieties and their interrelationships were studied during 2005-06. Only 4 varieties of Indian mustard (’Bio 902’, ’CS 54’, ’GM 2’ and ’Uravashi’) had 1000-seed weight more than 6 g. Oil and protein content were the least variabie with coefficient of variability of 3.5 % and 4.5 % respectively. Oleic acid content in majority of the varieties (66) was < 15.0%. Three varieties of gobhi sarson ’GSC 5’, ’TERI (OE) R 03’ and ’TERI (00) R 9903’ had high oleic acid (59.7-66.9%). Six varieties had >25.0% Iinoleic acid. Linolenic acid in 70 varieties was I 18.0%. Except 3 varieties of gobhi sarson [’GSC 5’, ’TERI (OE) R 03’ and ’TERI (00) R 9903’1 and 1 variety of Indian mustard (’Pusa Karishma’), the rest of the varieties had substantial amount of erucic acid (30.1-57.3%). Glucosinolate content was in the range of 75.1-120.3 p moleslg defatted seed meal and only 4 varieties of gobhi sarson and ’RCC 4’ Indian mustard had < 50 p moles glucosinolate content. Erucic acid showed positive and significant association with glucosinolate content.